Akuntansi Keuangan dalam Era Digital: Peran Teknologi Blockchain dan AI dalam Transparansi dan Akuntabilitas - Handarini, Dwi; Anugrah, Surya; Suyono, Windy Permata; Puspa, Eka Septariana (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
The development of digital technology has changed various aspects of financial accounting, particularly in terms of transparency and accountability. Two key technologies that have the potential to revolutionise modern accounting systems are Blockchain and Artificial Intelligence (AI). Blockchain offers a secure, transparent, and immutable record-keeping system, while AI is able to automate the analysis of large amounts of data and detect suspicious patterns. This article aims to review the literature related to the implementation of Blockchain and AI in financial accounting and analyse their impact on transparency and accountability. The review shows that although these two technologies have great benefits, there are still various challenges such as immature regulations, limited technological infrastructure, and the readiness of human resources in the accounting industry.